Effect of HbDHN1 and HbDHN2 Genes on Abiotic Stress Responses in Arabidopsis - Cao, Yuxin; Xiang, Xian; Geng, Mengting; You, Qin; Huang, Xi (Frontiers in Plant Science, 2017)
Dehydrin is a type of late embryogenesis abundant (LEA) protein. The dehydrin genes, HbDHN1 and HbDHN2, in Hevea brasiliensis were previously found to be induced at the wounding site of epicormic shoots, with local tissue dehydration identified as the key signal for laticifer differentiation. However, the exact role of the HbDHNs remains unknown. In this study, HbDHN1 and HbDHN2 expression was examined under multiple abiotic stresses; namely, cold, salt, drought, wounding, abscisic acid (ABA), ethylene (ET) and jasmonic acid (JA) treatment. Although both HbDHNs were defined as SK2-type dehydrin, they showed different cellular localizations. Overexpression of the HbDHNs in Arabidopsis thaliana further revealed a significant increase in tolerance to salt, drought and osmotic stresses. Increased accumulation of proline and a reduction in electrolyte leakage were also observed under salt and drought stress, and a higher water content was indicated under osmotic stress. The transgenic plants also showed higher activity levels of ascorbate peroxidase (APX), superoxide dismutase (SOD) and catalase, and accumulated less hydrogen peroxide (H2O2) and superoxide (O2-). Given that reactive oxygen species (ROS) are thought to be a key signal for laticifer differentiation, these findings suggest that HbDHNs act as ROS scavengers, directly or indirectly affecting laticifer differentiation. Both HbDHNs therefore influence physiological processes, improving plant tolerance to multiple abiotic stresses.